Aqueous seeded RAFT polymerization for the preparation of self-assemblies containing nucleobase analogues [data] - Abad, Miriam; Nardi, Martina; Oriol, Luis; Piñol, Milagros; Blasco, Eva (Universität, 2023)
Self-assemblies containing the nucleobase analogue 2,6-diacylaminopyridine (DAP) have been successfully prepared for the first time by aqueous seed...
Gesehen am 09.03.2023
Keywords: Forschungsdaten; Datenbank